Implantable Cardioverter-Defibrillators for Primary Prevention of Sudden Cardiac Death in Patients with Left Ventricular Systolic Dysfunction: 14 Years after MADIT - Franqui-Rivera, Hilton; Sotomonte, Juan C. (Puerto Rico Health Sciences Journal, 2011)
Sudden cardiac death (SCD) is the most common cause of death among patients with heart failure and left ventricular systolic dysfunction. Implantable cardioverterdefibrillators (ICDs) have been shown to be the single most effective therapy for primary prevention of SCD in patients with heart failure. The superiority of this therapy was clearly established for patients with ischemic cardiomyopathy by large clinical trials, such as the Multicenter Automatic Defibrillator Implantation Trial (MADIT), Multicenter Unsustained Tachycardia Trial (MUSTT), and MADIT-II studies. On the other hand, there was much debate on whether these results could be extrapolated for patients with non-ischemic cardiomyopathy until the Sudden Cardiac Death in Heart Failure Trial (SCD-HeFT) demonstrated a significant benefit of this therapy. Given the high costs of this therapy and the limited resources allocated to health care multiple studies have attempted to identify patients at higher risk of suffering SCD, who in theory will benefit the most out of this therapy. However, these studies have not established a reliable way to predict which patients will receive a direct survival benefit from ICD therapy. Until we are capable of further defining which patients will derive the absolute highest benefit from an ICD, we must rely on the information available from published trials and adhere to current clinical practice guidelines regarding this pressing issue.